Aktualisasi Diri dan Nilai Pendidikan dalam Novel Dendam Si Yatim Piatu Karya Sintha Rosse - Julia Julia; Zaenal Arifin (Neolectura, 2020)
This study aims to analyze self-actualization and educational values contained in Sintha Rosse's Dendam si Yatim Piatu novel based on Abraham Maslow's humanistic psychology. The research method used was descriptive qualitative method and content analysis technique. The results showed: 1) Self-actualization was found to be more dominant in this novel as much as 65.08% while the value of education was 34.91%. The 14 characters who show self-actualization are found all in this novel. The most dominant self-actualization is focusing on achievement targets (13.52%), the second most is social awareness (13.09%), independence (9.23%), spontaneity, simplicity, and fairness (9.01%). rewards that are always new (8.80%), interpersonal relationships (8.80%), creativity (6.87%), democratic (6.01%), self-acceptance (5.79%), independence (5.58 %), peak experience (4.29%), observing reality efficiently (3.43%), a meaningful sense of humor (3.00%), and the need for privacy (2.58%). 2) The dominant educational value is the value of moral education (37.20%), followed by the value of social education (29.60%), the value of divine education (24.40%), the value of cultural education (5.60%), and the value of aesthetic education (3.20%). Through this novel, the author provides an example through self-actualization of the main character, maximizing all efforts, developing talents, potential, never giving up in achieving goals and achieving the desired success so that life becomes more meaningful. In addition, the author also conveys good values so that readers can wisely take lessons from them which are expected to be applied in everyday life.